Reframing rhetorical history : cases, theories, and methodologies - Turner, Kathleen J., 1952-; Black, Jason Edward (The University of Alabama Press, 2022)
"Reframing Rhetorical History both reassesses history as rhetoric and rhetorical history as practice. It attends to a number of topics that have become not just "hot button" issues in rhetorical scholarship over the ensuing two decades, but which have entrenched themselves as anchors within the field, among them digital rhetoric, public memory, race and ethnicity, gender dynamics and sexualities, dis/abilities, health and well-being, environmentalism, transnationalism and globalization, social justice, archival methods and archival politics, performance theory, and colonialism and decoloniality. The sixteen essays are divided into four major parts. "Digital Humanities and Culture" introduces methods and cases involving 21st century technologies; the chapters here address the profundity, utility, and limitations of data science, digital archiving, and social media in both gathering rhetorical-historical texts and analyzing them as a method. "Subject Positionality, Culture, and Archives" addresses race and gender within the contexts of critical race theory, gendered health rhetoric, race-based public memory, and class/sectionalism. It also offers fresh perspectives on the nature of archives, positing them less as stagnant, dusty repositories and more as sources of power-laden ideas and living and breathing bodies of resistive agency. The third section explores post-9/11 ideologies related to U.S. and international cultures. Titled "Approaches to Nationalism and Transnationalism," this collection of chapters explores nationalistic fervor and fragility in cases of colonial states, border politics, citizenship, legal imperialism, and remembering. The fourth section, "Recovery of Rhetorical History in the Corpus and Classroom" explores creative ways to recover history given what the field has learned since the publication of Doing Rhetorical History. Cases here aim to retrieve lost rhetorical-historical documents and to work the study of rhetorical history into 21st century classrooms"-- Provided by publisher.
Keywords: Speeches, addresses, etc., American -- History and criticism.; Communication in politics -- United States -- History -- Case studies.; English language -- United States -- Rhetoric -- Case studies.; Rhetoric -- Political aspects -- United States -- History -- Case studies.; Rhetoric -- Social aspects -- United States -- History -- Case studies.; United States -- Historiography.; Discours américains -- Histoire et critique.; Communication politique -- États-Unis -- Histoire -- Études de cas.; Anglais (Langue) -- États-Unis -- Rhétorique -- Études de cas.; Discours politique -- États-Unis -- Histoire -- Études de cas.; Rhétorique -- Aspect social -- États-Unis -- Histoire -- Études de cas.; LANGUAGE ARTS & DISCIPLINES / Rhetoric.; LANGUAGE ARTS & DISCIPLINES / Communication Studies.; Speeches, addresses, etc., American; Rhetoric -- Social aspects; Rhetoric -- Political aspects; Historiography; English language -- Rhetoric; Communication in politics; United States; History; Criticism, interpretation, etc.; Case studies